2021
DOI: 10.21203/rs.3.rs-445040/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Case-Control Study of Factors Associated with SARS-CoV-2 Infection Among Healthcare Workers in Colombia.

Abstract: Background: Healthcare Workers (HCW) are repeatedly exposed to SARS-CoV-2 infection. The aim of this study was to identify factors associated with SARS-CoV-2 infection among HCW in one of the largest cities in Colombia. Methods: We conducted a case-control study, where cases had a positive reverse transcription-polymerase chain reaction and controls had a negative result. Participants were randomly selected and interviewed by phone. Analyses were performed using logistic regression models. Results: A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
(36 reference statements)
2
5
0
Order By: Relevance
“…We explored the occupation of HCWs as a possible risk factor associated with SARS-CoV-2. In our study, being a nurse increased the risk of SARS-CoV-2 infection by 20% compared with being an administrative HCWs, which is consistent with the results of studies in different countries [ 32 34 ]. We found a lower risk of infection in physicians than in administrative HCWs, which is unusual from the trend in the literature [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We explored the occupation of HCWs as a possible risk factor associated with SARS-CoV-2. In our study, being a nurse increased the risk of SARS-CoV-2 infection by 20% compared with being an administrative HCWs, which is consistent with the results of studies in different countries [ 32 34 ]. We found a lower risk of infection in physicians than in administrative HCWs, which is unusual from the trend in the literature [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…We observed a reduction in the risk of SARS-CoV-2 infection in the HCWs who used N-95 respirators compared with the risk in those who used surgical or cloth masks, which has been reported previously [ 32 , 43 ]. In addition, recent research regarding airborne transmission suggests that N95 respirators may be preferable for all HCWs activities [ 44 ].…”
Section: Discussionsupporting
confidence: 85%
“…Meanwhile, inconsistent with the study performed by Atnafie et al, 2021 24 who reported that age between 25 and 34 years (AOR = 0.20), age between 35 and 44 years (AOR = 0.13), family size of >6 (AOR = 3.77), and work experience of 21-30 years (AOR = 0.01) were the protective factors against COVID-19. Meanwhile, Rodriguez-Lopez et al, 2021 18 detected those men (AdjOR 4.13, 95% CI 1.70-10.05) and nurses (AdjOR 11.24, 95% CI 1.05-119.63) were identified as risk factors for infection among health workers.…”
Section: Discussionmentioning
confidence: 99%
“…Participants: The size of the sample was computed with a confidence rate of 95%, power 0.8, the odds ratio was 11.24, 18 and the expected proportion in controls was 0.01. Ten percent of the non-response rate was added, and the minimum sample size per group was 97 nurses.…”
Section: Methodsmentioning
confidence: 99%
“…Nineteen studies compared the effectiveness of different types of masks for reducing transmission of SARS-CoV-2: four studies (two RCTs, two observational) in community settings [14,16,23,47] and 15 studies (one RCT, 14 observational) in healthcare settings [50,52,57,68,[70][71][72][73][74]78,80,[82][83][84]88].…”
Section: (B) Comparative Effectiveness Of Different Types Of Masksmentioning
confidence: 99%